Agricultural growth, efficiency and family agriculture in Paraguay - Nin-Pratt, Alejandro (International Food Policy Research Institute, 2018)
Between 2001 and 2012, Latin America and the Caribbean’s (LAC) agriculture saw its best performance of the last 30 years. What were the implications of this growth for family agriculture (FA) in the region? This study contributes to answer this question by looking at the case of Paraguay, a country with one of the fastest growing agricultural sectors in the region during this period. At the center of the development challenges faced by this country is the debate on the role of family agriculture and smallholders in a future growth strategy. Between 1991 and 2008 the number of family workers in agriculture decreased significantly, while the total area of FA crops decreased to only 48 percent of its level in 1991. As some authors argued in the past, the 2000s represent a turning point for FA development in Paraguay, given that until 2002, the total area of farms of less than 20 hectares was still increasing, a trend that reversed after this year. Are these changes, part of a process of impoverishment of the rural population resulting from displacement of FA by the commercial sector as is normally assumed in previous studies? Evidence from this study shows that rural poverty decreased almost by half between 2003 and 2015; that the reduction of output of crops traditionally produced by FA was not the result of competition with the commercial sector, but mostly a consequence of the collapse of cotton production, a failure of a government program for FA; and that in regions with high proportion of FA, commercial crop production expanded by displacing inefficient extensive livestock farmers and not FA agriculture. We conclude that the situation of FA in Paraguay is much more diverse and complex than the simple claims of decomposition and disappearance as the result of the expansion of capitalist farmers. In this context, there are options for the government to promote the development of FA with the goal of increasing employment opportunities in rural areas while achieving a much-needed diversification of agricultural production and exports.